DEEP ECOLOGY DALAM PEMIKIRAN ARNE NAESS (ANALISIS ETIKA LINGKUNGAN) - Dewi Kusuma Ningsih, Riana (Sulesana: Jurnal Wawasan Keislaman, 2026)
The background of this research is the increasing global environmental crisis, such as climate change, deforestation, pollution, and the exploitation of natural resources caused by the anthropocentric view that places humans as the center of everything. Arne Naess offers a new paradigm through the concept of Deep ecology which emphasizes that humans are part of nature and all living things have value that needs to be respected. Thus, this research focuses on questions regarding the background of Arne Naess's Deep ecology, the framework of Deep ecology's thinking, and its relevance in the analysis of environmental ethics. This research applies a qualitative method with a literature study approach and philosophical analysis. The philosophical approach is applied to evaluate the concepts, values, and basic thinking of Arne Naess regarding Deep ecology, while the hermeneutic approach is used to interpret the meaning contained in his works. Primary data sources come from Arne Naess's writings related to Deep ecology and environmental ethics, while secondary data are obtained from books, journals, scientific articles, and relevant previous studies. Data collection techniques are carried out through systematic literature searches and analyzed using descriptive, interpretative, deductive, and inductive methods. The results of the study indicate that Deep ecology is a philosophical perspective that views humans as elements within the entire ecosystem. Arne Naess rejects the view that places humans at the center and asserts that every living creature has intrinsic value. The ideas of self-realization and ecosophy form the basis of human ecological awareness, enabling harmonious interaction with nature. This research also indicates that environmental problems arise from human perspectives that exploit nature.